2015
DOI: 10.1039/c5ra02278a
|View full text |Cite
|
Sign up to set email alerts
|

Nano-caged shikimate as a multi-site cross-linker of collagen for biomedical applications

Abstract: Shikimic acid caged silver nanoparticles as multi-site cross-linkers of collagen for tissue engineering applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Shikimic acid has also found its use in material science as an additive in the stabilization of metal nanoparticles and cross-link collagen for use in tissue engineering applications . Banach and Pulit-Prociak prepared a series of metal nanoparticles by chemical reduction with tannic and shikimic acids, sodium salicylate, or sodium potassium tartrate as reducing and stabilizing agents.…”
Section: Miscellaneous Applications Of Shikimic Acidmentioning
confidence: 99%
See 2 more Smart Citations
“…Shikimic acid has also found its use in material science as an additive in the stabilization of metal nanoparticles and cross-link collagen for use in tissue engineering applications . Banach and Pulit-Prociak prepared a series of metal nanoparticles by chemical reduction with tannic and shikimic acids, sodium salicylate, or sodium potassium tartrate as reducing and stabilizing agents.…”
Section: Miscellaneous Applications Of Shikimic Acidmentioning
confidence: 99%
“…Additionally, shikimic acid caged silver nanoparticle stabilized collagen showed cell proliferative and antimicrobial properties. Surprisingly, even though shikimic acid is engineered and produced in E. coli , its conjugation with silver nanoparticles resulted in microbial growth inhibition …”
Section: Miscellaneous Applications Of Shikimic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…However, once the concentration of AgNPs exceeded the critical point (i.e., the A/P ratio exceeded 1 : 10), the crash between AgNPs increased rapidly, which offset the dispersive power and the protection of the EPS to AgNPs. 31,32 The band at 1000-1200 cm À1 was attributed to the C-O antisymmetric stretching in the C-O-H and C-O-C groups of polysaccharides. 30 The FT-IR could provide the information about the interactions between molecules.…”
Section: Synthesis Of Agnpsmentioning
confidence: 99%
“…The broad peak at 3300-3450 cm À1 was assigned to the stretching vibrations of O-H and a weak peak at 2924 cm À1 was an indication of the C-H stretching vibrations of polysaccharide. 31,32 The band at 1000-1200 cm À1 was attributed to the C-O antisymmetric stretching in the C-O-H and C-O-C groups of polysaccharides. 33,34 It can be clearly observed that the characteristic absorption peak of OH for the pure EPS was at 3439 cm À1 , while those for the EPS-Ag nanocomposites were in a higher wavenumber range (3450-3462 cm À1 ).…”
Section: Synthesis Of Agnpsmentioning
confidence: 99%